PENGELOLAAN PELAYANAN SOSIAL BERBASIS MASJID DALAM PERSPEKTIF EKONOMI ISLAM: STUDI KASUS DIVISI SOSIAL MASJID ASH-SHIDDIQ SIDOARJO - Andy Fahmi Halim; Muhammad Rifki Rizqullah; Angger Bimantara; Budi Santoso (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the socio-economic management of the Social Division of Ash-Shiddiq Mosque (DSM Ash-Shiddiq) from the perspective of Islamic economics. The study focuses on the transformation of mosque social functions, humanitarian service practices, implementation of ta’awun and maslahah values, operational sustainability strategies, and social impacts on the community. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observations, and documentation involving administrators, volunteers, and related parties. The analysis was conducted descriptively and interpretatively by linking empirical findings with Islamic economic perspectives. The findings reveal that DSM has transformed from a funeral assistance unit into a mosque-based social organization providing ambulance services, funeral management, social assistance, clean water pipeline projects, and disaster relief programs. These services are implemented through flexible and participatory mechanisms supported by inter-community volunteer networks such as Satda Indonesia, MBA, and AMI. DSM’s practices reflect the implementation of ta’awun, maslahah, and distributive justice through cross-subsidy mechanisms and community-needs-based services. Despite financial limitations, volunteer dependency, and bureaucratic barriers, DSM has maintained its sustainability through community solidarity and adaptive participation-based strategies.